POLA PERTUMBUHAN IKAN KELABAU (Osteochilus melanoplurus) DI SUNGAI KAMPAR, ROKAN HILIR dan SIAK, PROVINSI RIAU - Ayi Yustiati; Nur Asiah (Jurnal Akuakultur Rawa Indonesia, 2018)
ABSTRACTThe research aim to determine growth pattern of kelabau carp caught by sempirai net used in Kampar, Rokan Hilir and Siak River, Riau province. This research was conducted on April to July 2017 in Biologi Perikanan Laboratory Fisheries and Marine Faculty Universitas Riau. The method used in this research is survey with descriptive quantitative data analyze. Parameters observed includes distribution of total length, relation of length and weight, and condition factor. Kelabau carp which caught in Kampar Desa Teluk Paman as much as 26 fishes, in Kampar Desa Langam as much as 35 fishes, in Rokan Hilir as much as 52 fishes, in Siak as much as 12 fishes. Kelabau carp which caught in Kampar River has the smallest size 110 mm and the largest size of 472 mm, in Rokan Hilir River has the smallest size of 95 mm and the largest size of 315 mm, and in Siak river has the smallest size of 249 mm and the largest size of 510 mm. Relation of length and weight kelabau carp in Kampar Desa langam and Rokan Hilir River is allometrik positive it means the weight increase faster than the length. Condition factor kelabau carp in Kampar Desa Teluk Paman ranged from 2,48-2,77, in Kampar Desa Langam ranged from 1,24-4,96, in Rokan Hilir ranged from 1,21-2,99, and in Siak ranged from 0,77-1,11. Key words: Kelabau, growth, kampar, rokan hilir, siak